The Influence of Environmental Performance and Carbon Emission Disclosure on Firm Value with Profitability as a Mediating Variable - Ni Luh Gede Prita Enggie Cahyani; Ni Made Dwi Ratnadi (Digital Innovation : International Journal of Management, 2025)
Stock price fluctuations, particularly in the energy sector, reflect market uncertainty regarding corporate performance and sustainability commitments. A high stock price indicates strong firm value. This study aims to provide empirical evidence on the influence of environmental performance and carbon emission disclosure on firm value, with profitability as a mediating variable. The study was conducted on energy sector companies listed on the Indonesia Stock Exchange during 2021–2023. The sample was selected using purposive sampling, resulting in 165 observations. Path analysis and Sobel test were employed. The results indicate that both financial and non-financial disclosures by companies can serve as either positive or negative signals influencing investor perceptions in decision-making. This supports signaling theory, which emphasizes the importance of information transparency to reduce information asymmetry and build market trust. Thus, companies, especially in the energy sector, must improve the quality and reliability of their disclosures by preparing transparent, accurate, and standard-compliant reports to strengthen their public image and increase firm value.